Identification and functional characterization of complement regulator-acquiring surface protein 1 of the Lyme disease spirochetes Borrelia afzelii and Borrelia garinii - Wallich, Reinhard; Pattathu, Joseph George; Kitiratschky, Véronique; Brenner, Christiane; Zipfel, Peter F.; Brade, Volker; Simon, Markus M.; Kraiczy, Peter (Infection and immunity, 2005)
Complement regulator-acquiring surface protein 1 (CRASP-1) is the dominant factor-H-like protein 1 (FHL-1)- and factor-H-binding protein of Borrelia burgdorferi and is suggested to contribute to persistence of the pathogen. The prototype CRASP-1 of B. burgdorferi sensu stricto (CRASP-1Bb) has been formerly characterized. As shown recently, serum-resistant Borrelia afzelii strains express a unique FHL-1 and factor H-binding protein, designated CRASP-1Ba. Here, we describe for the first time the isolation and functional characterization of the gene encoding the full-length CRASP-1Ba of 28 kDa, which, upon processing, is predicted to be 26.4 kDa. CPASP-1Ba of B. afzelii spirochetes is associated with a genetic locus encoding the orthologous gbb54 gene family that maps to the linear plasmid of approximately 54 kb. Ligand affinity blotting techniques demonstrate that both native and recombinant CRASP-1Ba molecules strongly bind to FHL-1 and much more weakly to factor H. The FHL-1 and factor-H-binding site in CRASP-1Ba is shown to be localized to a 12-amino-acid residue domain at the C terminus of the protein. For comparison, the corresponding cspA-like gene(s) of a serum-sensitive Borrelia garinii strain has also been cloned and characterized. Most notably, two CRASP-1-related B. garinii proteins were identified; however, both molecules bind only weakly to FHL-1 and not at all to factor H. The present identification of the binding site of CRASP-1Ba represents an important step forward in our understanding of the pathogenesis of Lyme disease and may be helpful to design therapeutic regimens to interfere with complement evasion strategies of human pathogenic Borrelia strains.